PENGEMBANGAN AGRIBISNIS JERUK PAMELO “BAGENG TAJI” (CITRUS SP.) DI KABUPATEN PATI - Ariyanto, Shodiq Eko; Pujiwati, Rochbijatun (Jurnal Pertanian, 2021)
Orange (Citrus sp.) is a fruit commodity that has an important role in the world and domestic markets. This study aims to analyze the internal and external environment (IE), and to analyze the agribusiness development strategy of Pammelo Bageng Taji in Pati Regency. Sources of data come from primary data, namely observations, focus group discussions (FGD), interviews with Dispertannak resource persons, agricultural extension agents, farmer contacts, citrus farmers, community leaders, stakeholders, and secondary data from relevant documents. The results showed that the main priority of the agribusiness development of Pummelo Bageng Taji orange was the potential of the land that was owned by using the national superior variety of Pummelo Bageng Taji and supported by good market demand, so the citrus variety needed to be developed as agribusiness, with a Total Attractive Score (TAS) 6.01.